Physicochemical characterization of C-phycocyanin from Plectonema sp. and elucidation of its bioactive potential through in silico approach - Husain, Arbab; Farooqui, Alvina; Khanam, Afreen; Sharma, Shubham; Mahfooz, Sadaf; Shamim, Adeeba; Akhter, Firoz; Alatar, Abdulrahman A.; Faisal, Mohammad; Ahmad, Saheem (Cellular and Molecular Biology, 2022)
C-phycocyanin (C-PC), the integral blue-green algae (BGA) constituent has been substantially delineated for its biological attributes. Numerous reports have illustrated differential extraction and purification techniques for C-PC, however, there exists paucity in a broadly accepted process of its isolation. In the present study, we reported a highly selective C-PC purification and characterization method from nontoxic, filamentous and non-heterocystous cyanobacterium Plectonema sp. C-PC was extracted by freeze-thawing, desalted and purified using ion-exchange chromatography. The purity of C-PC along with its concentration was found to be 4.12 and 245 µg/ml respectively. Comparative characterization of standard and purified C-PC was performed using diverse spectroscopic techniques namely Ultra Violet-visible, fluorescence spectroscopy and Fourier transform infrared (FT-IR). Sharp peaks at 620 nm and 350 nm with UV-visible and FT-IR spectroscopy respectively, confirmed amide I bands at around 1638 cm-1 (C=O stretching) whereas circular dichroism (CD) spectra exhibited α-helix content of secondary structure of standard 80.59% and 84.59% of column purified C-PC. SDS-PAGE exhibited two bands of α and β subunits 17 and 19 kDa respectively. HPLC evaluation of purified C-PC also indicated a close resemblance of retention peak time (1.465 min, 1.234 min, 1.097 min and 0.905 min) with standard C-PC having retention peak timing of 1.448 min, 1.233 min and 0.925 min. As a cautious approach, the purified C-PC was further lyophilized to extend its shelf life as compared to its liquid isoform. To evaluate the bioactive potential of the purified C-PC in silico approach was attempted. The molecular docking technique was carried out of C-PC as a ligand-protein with free radicals and α-amylase, α-glucosidase, glycogen synthase kinase-3 and glycogen phosphorylase enzymes as receptors to predict the free radical scavenging (antioxidant) and to target antidiabetic property of C-PC. In both receptors free radicals and enzymes, ligand C-PC plays an important role in establishing interactions within the cavity of active sites. These results established the antioxidant potential of C-PC and also give a clue towards its antidiabetic potential warranting further research.